2008
DOI: 10.1038/nm1770
|View full text |Cite
|
Sign up to set email alerts
|

Persistent activation of an innate immune response translates respiratory viral infection into chronic lung disease

Abstract: To understand the pathogenesis of chronic inflammatory disease, we analyzed an experimental mouse model of a chronic lung disease that resembles asthma and chronic obstructive pulmonary disease (COPD) in humans. In this model, chronic lung disease develops after infection with a common type of respiratory virus is cleared to trace levels of noninfectious virus. Unexpectedly, the chronic inflammatory disease arises independently of an adaptive immune response and is driven by IL-13 produced by macrophages stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
525
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 484 publications
(562 citation statements)
references
References 37 publications
28
525
2
3
Order By: Relevance
“…27 Airway goblet cell formation can be efficiently induced by airway delivery of IL33, which leads to macrophage and lymphocyte production of IL13. 14,[30][31][32][33] To test if autophagy plays a role in cytokine-induced inflammation in vivo, we compared the response of wild-type (WT) and Atg16l1 hypomorphic (HM) mice (Atg16l1 HM/HM ) 27 following intranasal administration of IL33. Airways of control mice (na€ ıve vehicle treated) contained few if any detectable goblet cells.…”
Section: Il33-induced Airway Goblet Cell Hypertrophy In Atg16l1-deficmentioning
confidence: 99%
“…27 Airway goblet cell formation can be efficiently induced by airway delivery of IL33, which leads to macrophage and lymphocyte production of IL13. 14,[30][31][32][33] To test if autophagy plays a role in cytokine-induced inflammation in vivo, we compared the response of wild-type (WT) and Atg16l1 hypomorphic (HM) mice (Atg16l1 HM/HM ) 27 following intranasal administration of IL33. Airways of control mice (na€ ıve vehicle treated) contained few if any detectable goblet cells.…”
Section: Il33-induced Airway Goblet Cell Hypertrophy In Atg16l1-deficmentioning
confidence: 99%
“…In vivo counterparts of M2 macrophage polarization have been observed in tissue remodelling during ontogenesis [28], chronic inflammation [29][30][31][32][33][34][35][36][37][38][39][40][41][42], cancer [9,12,16,17], bacterial [43][44][45][46][47][48][49] and parasitic [50][51][52][53] infections. Evidence has also accumulated that polarized macrophages are more than mere spectators of immunopathology [35][36][37][38][39][40][41][50][51][52].…”
Section: Activation and Adaptive Responses Of Macrophagesmentioning
confidence: 99%
“…The issue of lineage of the actual effectors of MDSC-mediated suppression is even more relevant when their recruitment and activation in non-lymphoid tissues is considered. For instance, do MDSC retain an immature phenotype in tumour tissues or do they differentiate into tumourassociated macrophages [9][10][11] [9,12,16,17], bacterial [43][44][45][46][47][48][49] and parasitic [50][51][52][53] infections. Evidence has also accumulated that polarized macrophages are more than mere spectators of immunopathology [35][36][37][38][39][40][41][50][51][52].…”
mentioning
confidence: 99%
“…[27][28][29][30][31][32] However, they can also contribute to the immunopathogenesis of viral diseases. For example, using an experimental mouse model of chronic lung disease triggered by infection with Sendai virus, Kim et al 33 demonstrated that IL-13 production by iNKT cells contributes to pulmonary disease. More recently, Stout-Delgado et al 34 demonstrated that IL-17 production by iNKT cells from aged mice infected with herpes simplex virus 2 is sufficient to promote liver damage and death.…”
Section: Discussionmentioning
confidence: 99%
“…20,24 -26 For example, during infection with influenza A virus, herpes simplex virus types 1 and 2, and lymphocytic choriomeningitis virus, iNKT cells have a positive role in anti-viral immune responses and virus-associated disease, [27][28][29][30][31][32] whereas during infection with Sendai virus and herpes simplex virus type 2 (only in aged mice), iNKT cells are rather deleterious. 33,34 However, iNKT cells do not seem to participate in anti-viral immunity or control of viral replication during infection with encephalomyocarditis virus and murine cytomegalovirus. [35][36][37] The potential role of iNKT cells in experimental viral infections has also been studied using CD1d-deficient mice, which lack both iNKT cells and vNKT cells.…”
mentioning
confidence: 99%